Annual movements of Interior Canada Geese Branta canadensis interior marked in Greenland, revealed by recoveries and re-sightings during 1992–2018 - Stroud, David A.; Cromie, Ruth; Crowe, Olivia; Denny, B.; Stroud, R. A.; Thomas, H.; Tierney, N.; Walsh, Alyn; Fox, Anthony D. (Wildfowl, 2018)
Analysis of 1,360 resightings and 105 recoveries made in continental North America during 1992–2018 of 542 Interior Canada Geese Branta canadensis interior marked in central-west Greenland in summers 1992, 1997, 2008, 2009 and 2014 were used to describe their winter quarters and the autumn and spring migration routes. Results showed that the geese arrived simultaneously in Newfoundland and Labrador, northeast Maine and central Nova Scotia in late September/October, but resightings and recoveries from Connecticut in September suggest that many may skip autumn staging and travel directly to be near their ultimate wintering site following arrival in continental North America. Some of the geese remained in northeast Maine and Nova Scotia into December, but the majority continued down into Massachusetts, Connecticut and especially Long Island in New York, which was the main wintering area for the marked individuals, with most occurring there during December–February inclusive. There were also resightings in January/February and recoveries in December/January from sites further south and west in New Jersey, Pennsylvania, Maryland and Delaware. Reports were too few to determine whether they constituted a regular movement, but there was no evidence that hard weather had displaced geese southwest from their core wintering areas, so it seems likely that some Canada Geese from Greenland do migrate to these areas each winter, which may represent their most distant winter quarters. By March, the Greenland Canada Geese had returned northwards and in the second half of the month aggregated in large numbers in the lower Richelieu Valley in Quebec. Very few birds were reported in Maine or Nova Scotia, in areas used in autumn, and there were no further records in continental North America after the first few days of May. Subtle differences between resightings and recovery distributions suggest differential spatial and temporal bias associated with both methods for describing the migration routes of Greenland’s Canada Geese. The Greenland-breeding interior race of Interior Canada Geese has close genetic affinities with the Atlantic Population of B. c. interior which breeds in northern Quebec and winters mostly in Delaware and Maryland. Despite some winter overlap of the two populations, these results support the continued inclusion of Greenland birds in current management of the North Atlantic Population of the Atlantic Canada Goose B. c. canadensis, which breeds in Newfoundland and Labrador and southeast Quebec, in that these populations of interior and canadensis Canada Geese use similar staging and wintering areas.